Blood Pressure and Risk of All-Cause Mortality in Advanced Chronic Kidney Disease and Hemodialysis: The Chronic Renal Insufficiency Cohort Study. Issue 1 (January 2015) - Bansal, Nisha; McCulloch, Charles E.; Rahman, Mahboob; Kusek, John W.; Anderson, Amanda H.; Xie, Dawei; Townsend, Raymond R.; Lora, Claudia M.; Wright, Jackson; Go, Alan S.; Ojo, Akinlolu; Alper, Arnold; et al.
Abstract : Studies of hemodialysis patients have shown a U-shaped association between systolic blood pressure (SBP) and mortality. These studies have largely relied on dialysis-unit SBP measures and have not evaluated whether this U-shape also exists in advanced chronic kidney disease, before starting hemodialysis. We determined the association between SBP and mortality at advanced chronic kidney disease and again after initiation of hemodialysis. This was a prospective study of Chronic Renal Insufficiency Cohort participants with advanced chronic kidney disease followed through initiation of hemodialysis. We studied the association between SBP and mortality when participants (1) had an estimated glomerular filtration rate <30 mL/min/1.73 m 2 (n=1705), (2) initiated hemodialysis and had dialysis-unit SBP measures (n=403), and (3) initiated hemodialysis and had out-of-dialysis-unit SBP measured at a Chronic Renal Insufficiency Cohort study visit (n=326). Cox models were adjusted for demographics, cardiovascular risk factors, and dialysis parameters. A quadratic term for SBP was included to test for a U-shaped association. At advanced chronic kidney disease, there was no association between SBP and mortality (hazard ratio, 1.02 [95% confidence interval, 0.98–1.07] per every 10 mm Hg increase). Among participants who started hemodialysis, a U-shaped association between dialysis-unit SBP and mortality was observed. In contrast, there was a linear association between out-of-dialysis-unit SBP and mortality (hazard ratio, 1.26 [95% confidence interval, 1.14–1.40] per every 10 mm Hg increase). In conclusion, more efforts should be made to obtain out-of-dialysis-unit SBP, which may merit more consideration as a target for clinical management and in interventional trials. Abstract : Supplemental Digital Content is available in the text.